Icaritin Improves Antibody-Induced Thrombocytopenia in a Mouse Model by Regulating T-cell Polarization - Sun, Chenghong; Yang, Jian; Wang, Mingzhi; Pan, Lihong; Yao, Jingchun; Wang, Shenglan; Guo, Na; Li, Chunyan; Zhang, Guimin (Planta Medica, 2018)
Previous studies have shown that icaritin (ICT) has significant protective effects on immune thrombocytopenia (ITP), and the present study aimed to discuss the mechanism of this protective effect from the aspect of regulating T-cell polarization by an antibody-induced ITP mice model. Mice were given rat anti-mouse CD41 antibody (MWReg30) by intraperitoneal injection for 7 d to produce ITP model. At the same time, ICT was administrated at 10 mg/kg/d orally for 9 d. Peripheral blood platelets were counted by hematology analyzer. Spleen index was also tested. Spleen T-helper cell (Th), cytotoxic T-cell (CTL), Th1, Th2, Th17, regulatory T-cell (Treg), and follicular helper T-cell (Tfh) were quantified by flow cytometry. Serum Th1/Th2/Th17 cytokines were tested by mouse Th1/Th2/Th17 cytometric bead array (CBA) kit and transforming growth factor beta (TGF-β) were analyzed by enzyme-linked immunosorbent assay (ELISA) kit. The results indicated that ICT (10 mg/kg) protected against MWReg30-induced ITP, as evidenced by increased blood platelets and decreased spleen index. In addition, the imbalance of Th/CTL in ITP mice spleen was regulated by ICT. Meanwhile, ICT inhibited Th1, Th17, and Tfh and improved Th2 and Treg in ITP mice spleen. Furthermore, the results of CBA and ELISA suggested that ICT decreased serum Th1- and Th17-related cytokines and increased Th2 cytokines, as well as promoted the release of TGF-β. These results demonstrated that the protective effect of ICT on ITP was mediated by regulating T-cell polarization.
Keywords: Icaritin; immune thrombocytopenia; T-cell polarization; helper T-cell; cytotoxic T-cell